Attracting and retaining talent: a comparison between social enterprise and commercial startups in Brazil - Sotirova, Evdokiya Nikolaeva (2019)
The aim of this paper is to identify the challenges and coping practices for attracting and retaining talent in the specific cases of social enterprise and startups which do not have a clearly stated social purpose (which are referred to as 'commercial startups' in this paper) in Brazil. The two types of companies are comparable because most social enterprises in Brazil are startups and both types face similar problems. The central focus of the research are the questions 'What are the challenges of attracting and retaining talent for social enterprise and commercial startups in Brazil and what are the similarities and differences between the two types of companies on that matter?' In order to develop and answer them, existing literature on a number of related topics was reviewed with an emphasis on the subject of 'Challenges in Attracting and Retaining Talent'. A qualitative research approach was adopted. Ten companies were interviewed, being five social enterprise startups and five commercial startups in varying stages of development; six of the startups are headquartered in the city of São Paulo and four - in Salvador, Bahia. Twelve in-depth interviews with founders, key actors in the area of talent management of the companies, as well as current and former employees at the two types of startups were conducted. An exploratory research approach was applied to the end of analyzing the data. The analysis revealed a multitude of similarities between social enterprise and commercial startups in Brazil on the matter of attracting and retaining talent. Both types of companies do not consider attracting new employees as particularly challenging, provided that they are known in the environment where young talent is active. However, a common difficulty for both types of startups is finding people with specific hard skills. The limited budget for salaries was pointed out as problematic for attracting talent in commercial startups. Furthermore, 'financial security' was quoted often by founders of both kinds of startups as a substantial challenge for talent retention. The severity of the consequences of people leaving depends on the stage of development that the startup is in. The central finding is that the inherent, most significant factor for successfully selecting and retaining the right people at both social enterprise and commercial startups is the factor of the 'fit'. Namely, the fit between the company and the candidate/employee on three instances: 1) personality, 2) goals i.e. career goals and 3) ways to achieve these goals. The results of the research are expected to be useful to social enterprise and commercial startups in overcoming the challenges they face when dealing with talent management.